Distribution peculiarities of stray fields and magnetization near magnet singularities - Samofalov, V.N.; Belozorov, D.P.; Ravlik, A.G.; Aseev, A.S. (Functional Materials, 2017)
Distributions of both magnetization and stray fields near singularities of a permanent magnet with high uniaxial anisotropy have been studied. On the basis of calculations it is shown that in magnets with high magnetic anisotropy, strong stray fields H > 4πMs occurring near the edge of a magnet do not practically result in deviation of magnetization from easy axis if the quality factor of the magnetic material g = K/(2πMS²) is g > 10. In such magnet systems, the distribution of magnetization is close to homogeneous, and it is possible to use the method of "magnetic charges" for calculations of stray fields. It is shown that the stray field near an edge of a magnet takes finite values, and the presence of a singularity at the dependence of the tangent component of the stray field Hτ ~ Ms-ln(a/r) at r → 0 is related to macroscopic characteristics generally accepted in magnetism, namely the surface density of "magnetic charges" σ.